Perceived challenges and enablers to evaluating a whole systems approach initiative: Reflections of embedded researchers. - Lauren Clifford; Adam Mars; Oliver Hamer (PLoS ONE)
Physical inactivity remains a substantial public health concern, with complex socio-environmental factors contributing to increasing inactivity. Whole systems approaches to physical activity seek to address these complexities by promoting multi-component, place-based interventions. This study reflects on the experiences of three embedded researchers working within a whole systems approach initiative aimed at reducing physical inactivity in the United Kingdom. Researchers were embedded within a local authority and affiliated to a university whilst responsible for evaluating the effectiveness and efficacy of the whole systems approach initiative. Using a reflective journaling method, followed by inductive thematic analysis, the findings identified key challenges and enablers to evaluating the initiative. Key challenges included the perceived value of research and evaluation within the local authority, a lack of capacity to conduct evaluative activity, and the presence of confirmation and reporting bias within the wider delivery team. Key enablers included relationship-building, skill development, and protected time for evaluation and research activity. The findings suggest that institutions supporting embedded researchers should establish regular contact with the local authority, help to establish realistic expectations, and support researchers to overcome emerging challenges. Recommendations for researchers include developing robust relationships, setting out clear expectations, and ensure they have protected time at key points during the evaluation. Through these recommendations, researchers may be better prepared to overcome implementation challenges and improve the efficiency of the evaluation process.